(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2017)
Micro Small and Medium Enterprises (SMEs) in contemporary Greece have difficulties in overcoming their financial risks via the use of their risk management mechanisms. The main reason for this failure is the presence of several financial impediments which prevent such risk management mechanisms to perform efficiently enough. So, the aim of this research is to unveil these financial impediments while the research question is What are the financial impediments that interfere with the Greek SMEs risk management mechanisms? The method that was used was the survey one by the use of questionnaires which were distributed face to face and by email. The data was analyzed by the use of the Dedoose software following a qualitative approach. The findings showed that the SMEs that were investigated used only informal and non- sophisticated risk management mechanisms, while the financial impediments that prevented such mechanisms to operate efficiently enough were the general unstable financial and political climate, the capital controls and the SMEs limited access to bank financing. The results of this research can have very important societal implications as they can show to SMEs owners the importance of the implementation of the right risk management mechanisms, something which can lead them to sustainable development and to general societal prosperity on the long run.